PENGARUH KONDISI SOSIAL EKONOMI ORANG TUA TERHADAP MOTIVASI MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI PADA SISWA KELAS XII MADRASAH ALIYAH NEGERI 02 KAMPAR TAHUN AJARAN 2021/2022 - Anum, Syahidatul; Gusnardi, Gusnardi; RM. Riadi, RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to describe the influence of parents' socio-economic conditions on the motivation to continue their education to higher education in class XII Madrasah Aliyah Negeri 02 Kampar Academic Year 2021/2022. This research is a type of quantitative descriptive research, the research population is 121 students of class XII Madrasah Aliyah Negeri 02 Kampar Academic Year 2021/2022. The sampling technique in this research is simple random sampling, the total number of samples is 55 students. Data collection techniques using a questionnaire. Data analysis used simple regression analysis. The results of this study indicate that the socioeconomic conditions of parents have a significant effect on the motivation to continue their education to college.Key Words: Parents' Socio-Economic Condition, Motivation to Continuing Education